Investigation of the Effects of Various Severe Plastic Deformation Techniques on the Microstructure of Laser Powder Bed Fusion AlSi10Mg Alloy - Snopiński, Przemysław; Matus, Krzysztof; Hilšer, Ondřej (Materials (Basel, Switzerland), 2023)
In this paper, we present a complete characterization of the microstructural changes that occur in an LPBF AlSi10Mg alloy subjected to various post-processing methods, including equal-channel angular pressing (ECAP), KoBo extrusion, and multi-axial forging. Kikuchi transmission diffraction and transmission electron microscopy were used to examine the microstructures. Our findings revealed that multi-axis forging produced an extremely fine subgrain structure. KoBo extrusion resulted in a practically dislocation-free microstructure. ECAP processing at temperatures between 100 °C and 200 °C generated moderate grain refinement, with subgrain diameters averaging from 300 nm to 700 nm. The obtained data highlighted the potential of severe plastic deformation as a versatile method for tailoring the microstructure of the AlSi10Mg alloy. The ability to precisely control grain size and dislocation density using specific SPD methods allows for the development of novel materials with ultrafine-grained microstructures that offer the potential for enhanced mechanical and functional properties.
Keywords: AlSi10Mg; multi-axial forging; microstructure; ECAP; KoBo extrusion